Effect of neonatal melatonin administration on behavioral and brain electrophysiological and redox imbalance in rats - Araújo, Amanda de Oliveira; Figueira-de-Oliveira, Maria Luísa; Noya, Arthur Gabriel Alves Furtado de Carvalho; Oliveira e Silva, Vitor Palmares; Carvalho, Jennyfer Martins de; Vieira Filho, Leucio Duarte; Guedes, Rubem Carlos Araújo (Frontiers in Neuroscience, 2023)
Introduction Melatonin (MLT) reportedly has beneficial effects in neurological disorders involving brain excitability (e.g., Epilepsy and Migraine) and behavioral patterns (e.g., Anxiety and Depression). This study was performed to investigate, in the developing rat brain, the effect of early-in-life administration of two different doses of exogenous MLT on behavioral (anxiety and memory) and electrophysiological (CSD analysis) aspects of brain function. Additionally, brain levels of malondialdehyde (MDA) and superoxide dismutase (SOD), both cellular indicators of redox balance status, were evaluated. We hypothesize that MLT differentially affects the behavioral and CSD parameters as a function of the MLT dose. Materials and methods Male Wistar rats received, from the 7th to the 27th postnatal day (PND), on alternate days, vehicle solution, or 10 mg/kg/or 40 mg/kg MLT (MLT-10 and MLT-40 groups), or no treatment (intact group). To perform behavioral and cognition analysis, from PND30 to PND32, they were tested in the open field apparatus, first for anxiety (PND30) and then for object recognition memory tasks: spatial position recognition (PND31) and shape recognition (PND32). On PND34, they were tested in the elevated plus maze. From PND36 to 42, the excitability-related phenomenon known as cortical spreading depression (CSD) was recorded, and its features were analyzed. Results Treatment with MLT did not change the animals’ body weight or blood glucose levels. The MLT-10 treatment, but not the MLT-40 treatment, was associated with behaviors that suggest less anxiety and improved memory. MLT-10 and MLT-40 treatments, respectively, decelerated and accelerated CSD propagation (speed of 2.86 ± 0.14 mm/min and 3.96 ± 0.16 mm/min), compared with the control groups (3.3 ± 0.10 mm/min and 3.25 ± 0.11 mm/min, for the intact and vehicle groups, respectively; p < 0.01). Cerebral cortex levels of malondialdehyde and superoxide dismutase were, respectively, lower and higher in the MLT-10 group but not in the MLT40 group. Conclusion Our findings suggest that MLT intraperitoneal administration during brain development may differentially act as an antioxidant agent when administered at a low dose but not at a high dose, according to behavioral, electrophysiological, and biochemical parameters.